Molecular orientation-dependent energetic shifts in solution-processed non-fullerene acceptors and their impact on organic photovoltaic performance - Yuang Fu; Tack Ho Lee; Yi-Chun Chin; Richard A. Pacalaj; Chiara Labanti; Song Yi Park; Yifan Dong; Hye Won Cho; Jin Young Kim; Daiki Minami; James R. Durrant; Ji-Seon Kim (Nature Communications, 2023)
Non-fullerene acceptors with large quadrupole moments strongly affect thin-film energetics. Here, the authors show a significant energetic shift (>200 meV) of Y6 upon changing its orientation from face-on to more edge-on using different solvents and its critical impact on organic photovoltaics.